2009
DOI: 10.1016/j.jmb.2009.04.024
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Fluorescence Microscopy Reveals the Role of Selenium in Spermatogenesis

Abstract: Selenium (Se) is a trace element with important roles in human health. Several selenoproteins have essential functions in development. However, the cellular and tissue distribution of Se remains largely unknown because of the lack of analytical techniques that image this element with sufficient sensitivity and resolution. Herein, we report that X-ray fluorescence microscopy (XFM) can be used to visualize and quantify the tissue, cellular and subcellular topography of Se. We applied this technique to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 43 publications
0
53
0
1
Order By: Relevance
“…Consistent with the known importance of mGPx4 and TGR in latter spermatogenic stages, testicular histology in P1 showed maturation arrest, with preservation of early cell types (e.g., spermatogonia and spermatocytes) but lack of mature spermatids and spermatozoa ( Figure 2G). SEPP, acting as a source of selenium to meet tissue demand, has also been implicated in spermatogenesis, with SEPP-null mice showing abnormal sperm morphology and diminished testicular selenium content (30,31). Thus, markedly reduced circulating SEPP levels in P1 ( Figure 1B) may be an added factor contributing to his azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the known importance of mGPx4 and TGR in latter spermatogenic stages, testicular histology in P1 showed maturation arrest, with preservation of early cell types (e.g., spermatogonia and spermatocytes) but lack of mature spermatids and spermatozoa ( Figure 2G). SEPP, acting as a source of selenium to meet tissue demand, has also been implicated in spermatogenesis, with SEPP-null mice showing abnormal sperm morphology and diminished testicular selenium content (30,31). Thus, markedly reduced circulating SEPP levels in P1 ( Figure 1B) may be an added factor contributing to his azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Specific re-expression of SelP in the liver restores Se transport and rescues phenotypes associated with SelP deficiency (25). Using X-ray fluorescence microscopy (XFM), we recently showed that SelP provides testes with Se where it is used for synthesis of the mitochondrial form of glutathione peroxidase 4 (16,20).…”
mentioning
confidence: 99%
“…Historically, different substrates, ranging from thin polycarbonate foils/films [35][36][37] , formvar coated gold transmission electron microscopy (TEM) grids [38][39][40][41][42] and silicon nitride windows 5,17,[43][44][45][46] , have been used to grow mammalian cells and used for X-ray fluorescence imaging. In comparison among the existing and potential substrates for imaging adherent mammalian cells by XFM, silicon nitride membrane (Si 3 N 4 ) windows are most suitable due to their low fluorescence background and relatively simple elemental composition [4][5][6]47,48 . In addition Si 3 N 4 windows support robust cell attachment and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…With very high-intensity beams, even a relatively small amount of light that can be focused is sufficient to excite the endogenous metals in cells, producing signal that can be measured with currently available detector technology. Thus, studying the chemical biology of metals in the cell is one application in particular that makes use of many of the recent developments in this technique [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%